EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE TIME TOKEN ARENDS DALAM KETERAMPILAN BERBICARA PADA MATA KULIAH KAIWA IV - Mulyani, Mulyani; Aibonotika, Arza; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study is to describe the effectivenes of cooperative learning model type Time Token Arend for student’s speaking ability in Kaiwa IV Course. In this study, Kaiwa 4 Course was learned with Japanese Foundation (JF) Standard Learning Design. One of the difficulties that student had during Kaiwa 4 learning process was lack of motivation due to monotonous learning situation. Therefore, Time Token Arends method was applied to create a varied and creative learning atmosphere. This study is a weak experimental research with one group pretest posttest design. The object of this study was the students 2017/2018 class A of Japan Study Program in Faculty Teachers Training in Education at Riau University. The sampling technique that used in this study was Purposive Sampling Technique. Based on the result of the study, there is an improvement after the students get treatment with Time Token Arend Method. The students become more excited during Kaiwa IV learning process. Futhermore, vocabulary that used by students during speaking was more varied. This is also supported by the result of the statistical tests of pretest and posttest data that was conductedKey Words: Kaiwa, Time Token Arends, JF Standard